Knowledge and Awareness of Pre‐Exposure Prophylaxis Among Men in Sub‐Saharan Africa: A Scoping Review Protocol - Badru, Oluwaseun; Hlongwa, Mbuzeleni; Adeagbo, Oluwafemi Atanda (Health science reports, 2025)
ABSTRACT Introduction About 39.9 million people were living with HIV as of 2023, and HIV is more prevalent in sub‐Saharan Africa. Pre‐exposure prophylaxis (PrEP) is highly effective in HIV prevention. Despite the efficacy of PrEP, many persons, including men, do not have adequate knowledge and awareness of PrEP, and reviews on knowledge and awareness among men are scarce. This review aims to assess and synthesize the knowledge and awareness of PrEP among persons assigned as males at birth in sub‐Saharan Africa. Methods and Analysis The proposed scoping review will be conducted in accordance with the PRISMA Extension for Scoping Reviews (PRISMA‐ScR): Checklist and Explanation. The following information sources will be searched to retrieve relevant studies for this review: CINAHL, MEDLINE (Ovid), PubMed, SCOPUS, and Web of Science. Google Scholar, The Union Catalogue of Theses and Dissertations (UCTD) and SA ePublications via SABINET Online, WorldCat Dissertations and Theses via OCLC, ResearchGate, and American Doctoral Dissertations via EBSCOhost. All study designs, except existing reviews, will be included. All screenings ( screening and full‐text screening) and data extraction will be conducted independently by two reviewers. Quantitative findings will be presented with frequency and percentages, while qualitative thematic analysis will be used to analyze qualitative findings. Conclusion This study will map out studies on knowledge and awareness of PrEP among men in sub‐Saharan Africa. The results of this review will give insights into what men in sub‐Saharan Africa know about PrEP, which can inform future interventions.